2022
DOI: 10.33369/joall.v7i1.19867
|View full text |Cite
|
Sign up to set email alerts
|

EFL students’ motivation on learning English: What can we learn from them?

Abstract: This study aimed to determine the students' motivation of non-English Department—intrinsic and extrinsic—in learning English. It was carried out at the second-grade students of the Quran Science and interpretation study program (IAT) academic year 2020/2021. This study employed descriptive-survey research. There were 34 students becoming the participants of this study.  The researchers employed the questionnaire, which consisted of twelve statements to get the data about students’ motivation. it was divided to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…That was done by conceptualizing their learning methods, trying to be consistent in achieving their goals, using free time to learn English from social media on YouTube, podcasts, spotify, etc, and holding discussions with classmates. Contrarily, Erniyati & Putra (2022) found that non-English department students' intrinsic motivation in learning English online was higher than their extrinsic motivation. Most students agreed that English is now substantial to master as it can help them achieving their dream job.…”
Section: Discussionmentioning
confidence: 94%
“…That was done by conceptualizing their learning methods, trying to be consistent in achieving their goals, using free time to learn English from social media on YouTube, podcasts, spotify, etc, and holding discussions with classmates. Contrarily, Erniyati & Putra (2022) found that non-English department students' intrinsic motivation in learning English online was higher than their extrinsic motivation. Most students agreed that English is now substantial to master as it can help them achieving their dream job.…”
Section: Discussionmentioning
confidence: 94%
“…This shows that they are aware that English is an important subject and must be mastered. With awareness from within the individual student, it will be a capital for students to get grades or achievements in English language learners (Aminah & Anjar Nugraha, 2021;Kholifah et al, 2021;Hu, 2022;Erniyati & Putra, 2022). While other students with other categories, namely "sufficient" (55 students) "low" Open Access: https://ejournal.unma.ac.id/index.php/educatio (21 students) and "very low" (1 student) can still be supported again so that motivation can grow from within the individual.…”
Section: Resultsmentioning
confidence: 99%
“…Fengxiang Zang, Mei Tian, Jingwei Fan, and Ying Sun (2022) conducted a study with international students at a Chinese university, which found that international students had high internal motivation for participation and integration in Chinese language learning (Zang, Tian, Fan, & Sun, 2022). Yelni Erniyati and Pristian Hadi Putra (2022) found that ESL students have high levels of intrinsic and extrinsic motivation, and students' intrinsic motivation is more elevated than extrinsic motivation (Erniyati, & Putra, 2022). Kumala Dewi (2020) took Chinese language department students in Bunda Mulia University Indonesia as object to do the research, and found that the learning motivation of UBM student is rather high.…”
Section: Related Literaturesmentioning
confidence: 99%